2018
DOI: 10.37358/rc.18.5.6284
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Immune Response in the Presence of a Cytotoxic Peptide

Abstract: We evaluated, by the flow cytometry technique, the viability of two tumor cell lines: colorectal carcinoma (HT-29) and human A549 arcinoma incubated with the cytotoxic peptide LL-37. The results obtained for the two cell lines HT-29 and A549 are significantly different under the action of cathelicidin LL-37. At high concentrations of 20mM, cellular apoptosis was over 30% higher for colorectal adenocarcinoma line compared to that by peptide exposure. Apoptosis was also significant in low-concentration (4uM) cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The inflammatory biomarkers that make up the biological picture attest to the inflammation present in all cancers. 6 , 7 As the disease progressed, metabolic modifications 8 and hydroelectrolytic changes occurred, 9 and cholestasis syndrome worsened, indicating hepatic dysfunction. 10 Fejzić et al revealed that the CA 15–3 tumor marker was elevated in more than 90% of patients with advanced disease and metastasis to the lungs, bones or liver, and is the tumor-specific marker in diagnosis and especially monitoring of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory biomarkers that make up the biological picture attest to the inflammation present in all cancers. 6 , 7 As the disease progressed, metabolic modifications 8 and hydroelectrolytic changes occurred, 9 and cholestasis syndrome worsened, indicating hepatic dysfunction. 10 Fejzić et al revealed that the CA 15–3 tumor marker was elevated in more than 90% of patients with advanced disease and metastasis to the lungs, bones or liver, and is the tumor-specific marker in diagnosis and especially monitoring of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%